2023
DOI: 10.1097/sla.0000000000005801
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Mesh Placement During Formation of an End-colostomy

Abstract: Objective: The aim of this study was to determine if prophylactic mesh placement is an effective, safe, and cost-effective procedure to prevent parastomal hernia (PSH) formation in the long term. Background: A PSH is the most frequent complication after stoma formation. Prophylactic placement of a mesh has been suggested to prevent PSH, but long-term evidence to support this approach is scarce. Methods: In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…57 However, at 5 years after surgery, there was no difference in either hernia rates (28 vs. 37%, p ¼ 0.22) or quality of life, suggesting that mesh may delay but not prevent hernia formation. 36 Similar findings were recently reported from the GRECCAR 7 trial involving 200 patients at 18 hospitals in France (31 vs. 28% at 2 years after surgery, p ¼ 0.77) 58 and the STOMAMESH trial involving 240 patients at 8 hospitals in Sweden (39 vs. 37% at 3 years after surgery, p ¼ 0.83). 35,59 Interestingly, no major study found higher rates of perioperative complications associated with mesh implantation, including surgical site infections.…”
Section: Late Complications Parastomal Herniasupporting
confidence: 78%
See 1 more Smart Citation
“…57 However, at 5 years after surgery, there was no difference in either hernia rates (28 vs. 37%, p ¼ 0.22) or quality of life, suggesting that mesh may delay but not prevent hernia formation. 36 Similar findings were recently reported from the GRECCAR 7 trial involving 200 patients at 18 hospitals in France (31 vs. 28% at 2 years after surgery, p ¼ 0.77) 58 and the STOMAMESH trial involving 240 patients at 8 hospitals in Sweden (39 vs. 37% at 3 years after surgery, p ¼ 0.83). 35,59 Interestingly, no major study found higher rates of perioperative complications associated with mesh implantation, including surgical site infections.…”
Section: Late Complications Parastomal Herniasupporting
confidence: 78%
“…12 Other studies report similar figures, with rates ranging from 2 to 28% for ileostomies and 0 to 48% for colostomies. [29][30][31][32][33][34][35][36] In general, loop stomas-especially loop colostomies-have a higher rate of parastomal hernia formation than end stomas, almost certainly due to size of the fascial defect needed to bring both ends of the intestine through the abdominal wall. Although there is no widely accepted criteria for sizing the fascial defect, most colorectal surgeons recommend keeping the opening as small as possible while still allowing the easy passage of the tip of a finger alongside the intestine since larger openings are associated with higher rates of parastomal hernia.…”
Section: Late Complications Parastomal Herniamentioning
confidence: 99%
“…The author stated that 82 (67.8%) individuals developed a parastomal hernia diagnosed by computed tomography. PMP did not lower the hernia rate [2,9,10,16]. On the other hand, the amount of analyzed individuals is low.…”
Section: Discussionmentioning
confidence: 99%
“…We identi ed 13 relevant randomized clinical trials, and a total of 6 were published after GPTPH2017. Two trials were funded by the industry and a PMP was not recommended by these authors [9,17]. Four trials did not report information on funding to the best of our knowledge, and in9 of the 13 trials the authors did not have any disclosures [4-6, 9, 11, 15, 17-19].…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of parastomal bulging and the known negative impact on patients' quality of life [11,12] stand in stark contrast to the current lack of good prevention and treatment options surgically and non-surgically. Although prophylactic mesh may delay the onset of parastomal hernia in patients with an end colostomy [13][14][15][16], the application of prophylactic meshes in clinical practice is low [17]. For non-surgical preventive interventions, for example physical or abdominal training, lifting restrictions or wearing support garments, there is no firm evidence [18].…”
mentioning
confidence: 99%